The association between the socioeconomic status and body pain: A nationwide survey - Yu, Tong; Wei, Zhen; Xu, Tan; Gamber, Michelle; Han, Jingnan; Jiang, Yan; Li, Jian; Yang, Daihe; Sun, Wenjie (Medicine (Baltimore), 2020)
Pain is a significant burden among different communities, but little is known regarding the epidemiology of pain, particularly with respect to socioeconomic status (SES).The aim of the study was to estimate the prevalence of body pain and to identify risk factors of pain in middle-aged and older Chinese.The data were extracted from the 2008 Chinese Suboptimal Health Study that consisted of 18,316 Chinese subjects aged 18 to 65 years. Information on SES including occupation and education levels and body pain were collected. A Likert scale was used to evaluate reported body pain. We used the multiple logistic regression model to examine the association between SES and body pain.Overall, 65.34% reported body pain (male: 60.93%; female: 69.73%). After adjustments based on sex, age, education, area of residence, marital status, smoking, drinking and health status, the results showed that students (odds ratio [OR] = 1.51; 95% confidence interval [CI]: 1.32-1.74) and professionals (OR = 1.22; 95% CI: 1.08-1.37) had significant high risk for body pain, compared with civil servants and farmers (OR = 0.64; 95% CI: 0.55-0.75) who significantly lower risk of body pain. The study demonstrates there is a significant negative association between education and reported body pain.The results indicated an association between SES and body pain within the Chinese community. Body pain varied among different Chinese occupation-related population and people with higher education level are less like to have body pain.